2017
DOI: 10.1088/1361-6463/aa6f40
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer etching of silicon dioxide using alternating C4F8and energetic Ar+plasma beams

Abstract: Atomic layer etching (ALE) of SiO 2 was studied by alternating exposure of a 5 nm-thick SiO 2 film on Si substrate to (1) a plasma beam emanating from a cC 4 F 8 inductively coupled plasma (ICP), to grow a fluorocarbon (FC) film composed mainly of CF 2 , and (2) an energetic (130 eV) Ar + ion beam extracted from a separate Ar ICP. In situ x-ray photoelectron spectroscopy was used to analyze the chemical composition of the near-surface region, and to quantify the thickness of the FC and SiO 2 films. A very thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…One of the main solutions to perform anisotropic ALE of SiO 2 is to use fluorocarbon-based plasmas to deposit a very thin FC modified layer on the surface. This layer can then be etched using Ar or O 2 plasma at low ion energy bombardment 2,3,[6][7][8][9][10][11] . However, some drifts were reported in the processes, with an increase of the etch amount per cycle (EPC) due to the fluorine contamination of the reactor walls [8][9][10]12 .…”
mentioning
confidence: 99%
“…One of the main solutions to perform anisotropic ALE of SiO 2 is to use fluorocarbon-based plasmas to deposit a very thin FC modified layer on the surface. This layer can then be etched using Ar or O 2 plasma at low ion energy bombardment 2,3,[6][7][8][9][10][11] . However, some drifts were reported in the processes, with an increase of the etch amount per cycle (EPC) due to the fluorine contamination of the reactor walls [8][9][10]12 .…”
mentioning
confidence: 99%
“…These sticking coefficients are similar to those obtained recently by Kaler et al in cyclic plasma beam exposure experiments. 51 The transfer of ion energy through the polymer overlayer to the etch front is critical to this etch mechanism. Which energetic particles carry the activation energy to the etch front is difficult to analyze.…”
Section: Surface Reaction Mechanism For Sio 2 Si 3 N 4 and Smentioning
confidence: 99%
“…Kaler et al have also observed this effect and proposed that it may be utilized to produce pseudo-self-limiting behavior. 51 The second process which results in the erosion of SiO 2 occurs during the ion bombardment phase. This erosion occurs as SiO 2 is converted to selvedge species by mixing with polymer when activated by ions penetrating through the polymer capping layer.…”
Section: Ale Blanket Etchingmentioning
confidence: 99%
“…Using these techniques, a precise etch depth/cycle of various semiconductor related materials such as Si, III‐V compounds, metals, and 2D materials has been achieved . As the plasma sources for radical adsorption, inductively coupled plasma (ICP) and capacitively coupled plasma (CCP) were mainly used while, as the desorption sources, an ion/neutral beam or conventional radio frequency (RF) biasing was used for anisotropic ALE technology. Recently, for the fabrication of nanoscale devices, in addition to the anisotropic ALE, isotropic ALE or also known as thermal ALE, where, materials are etched the same in all direction isotropically, is actively investigated.…”
Section: Introductionmentioning
confidence: 99%